The Phragmites Root-Inhabiting Microbiome: A Critical Review on Its Composition and Environmental Application. (February 2022) - Wang, Donglin; Bai, Yaohui; Qu, Jiuhui
Graphical abstract: Abstract: As widespread wetland plants, Phragmites play a vital role in water purification and are widely utilized in constructed wetlands (accounting for 15.5% of applied wetland plants) as a natural alternative to wastewater treatment. However, despite such common applications, current understanding of the basic composition of the Phragmites root-inhabiting microbiome and the complex functions of each member of this microbiome remains incomplete, especially regarding pollution remediation. This review summarizes the advances that have been made in ecological and biochemical research on the Phragmites root microbiome, including bacteria, archaea, and fungi. Based on next-generation sequencing, microbial community compositions have been profiled under various environmental conditions. Furthermore, culture-based methods have helped to clarify the functions of the microbiome, such as metal iron stabilization, organic matter degradation, and nutrient element transformation. The unique community structure and functions are highly impacted by Phragmites lineages and environmental factors such as salinity. Based on the current understanding of the Phragmites root microbiome, we propose that synthetic microbial communities and iron–manganese plaque could be applied and intensified in constructed wetlands to help promote their water purification performance.